Passages - Richards, Jack C. (Cambridge University Press, 2008)
The Passages, Second Edition, Student's Books have been thoroughly revised to offer fresh, contemporary content, numerous opportunities for expansion of listening and speaking skills, reading skills development, plus a step-by-step academic writing strand. Vocabulary is now presented in every lesson and focuses on word building, collocations, and phrasal verbs. Communication Reviews every three units inlcude progress checks and additional speaking and listening activities. In the back of the Student's Books is a new Grammar Plus section with additional grammar explanation and practice, and a new learner-focused self-study section, containing academic listening practice and vocabulary building with dictionary skills practice. Also included in each Student's Book is a CD-ROM, containing both the Self-Study Audio from the Student's Book and the entire Cambridge Academic Content Dictionary